the Challenges of implementing social-emotional learning curricula in schools from the perspective of curriculum authors at the National Center for Curriculum Development (Journal of Hama University, 2026)
The aim of this study was to identify the challenges facing the implementation of the social-emotional learning curriculum in the Syrian Arab Republic from the perspective of teachers in the first stage of basic education, as well as to determine ways to overcome these challenges. The study also sought to analyze the differences in teachers' opinions based on variables such as educational qualification, years of experience, and the governorate in which they work. The sample consisted of 252 teachers from schools in the first stage of basic education. To achieve the study's objectives, a descriptive approach was used, and a questionnaire consisting of 26 items was prepared, distributed across two main axes: the challenges of implementing and executing the social-emotional learning curriculum in schools, and ways to overcome those challenges.The results showed that the average responses of teachers regarding the challenges faced in implementing the social-emotional learning curriculum in the cities of Damascus and Latakia ranged from high to very high. Among these challenges were the weak conviction of some teachers regarding the effectiveness of teaching the curriculum, insufficient training on its skills, lack of financial resources, and the unavailability of suitable educational environments for effective implementation.Regarding the second axis related to ways to overcome the challenges, the results also indicated that the average responses of teachers ranged from high to very high, suggesting a clear vision among them regarding possible solutions to these challenges. The study also indicated that there were no statistically significant differences between the average scores of teachers on the questionnaire based on the variables of educational qualification, years of experience, and governorate. In light of the results, the study recommended the need to develop intensive training programs for teachers focusing on social-emotional learning skills, taking into account diverse strategies to meet the varying needs of learners. It also recommended enhancing the partnership between schools and the community by involving parents and cultural institutions in supporting the social-emotional learning curriculum, in addition to conducting ongoing evaluations of its effectiveness and modifying it based on the obtained results
Keywords: : societal and emotional Learning